Fluorescent monitoring of copper-occupancy in His-ended catalytic oligo-peptides - Reina Inokuchi (Communicative & Integrative Biology, 2016)
Controlled generation of reactive oxygen species (ROS) is widely beneficial to various medical, environmental, and agricultural studies. As inspired by the functional motifs in natural proteins, our group has been engaged in development of catalytically active oligo-peptides as minimum-sized metalloenzymes for generation of superoxide anion, an active member of ROS. In such candidate molecules, catalytically active metal-binding minimal motif was determined to be X-X-H, where X can be most amino acids followed by His. Based on above knowledge, we have designed a series of minimal copper-binding peptides designated as GnH series peptides, which are composed of oligo-glycyl chains ended with C-terminal His residue such as GGGGGH sequence (G5H). In order to further study the role of copper binding to the peptidic catalysts sharing the X-X-H motif such as G5H-conjugated peptides, we should be able to score the occupancy of the peptide population by copper ion in the reaction mixture. Here, model peptides with Cu-binding affinity which show intrinsic fluorescence due to tyrosyl residue (Y) in the UV region (excitation at ca. 230 and 280 nm, and emission at ca. 320 nm) were synthesized to score the effect of copper occupancy. Synthesized peptides include GFP-derived fluorophore sequence, TFSYGVQ (designated as Gfp), and Gfp sequence fused to C-terminal G5H (Gfp-G5H). In addition, two Y-containing tri-peptides derived from natural GFP fluorophores, namely, TYG and SYG were fused to the G5H (TYG-G5H and SYG-G5H). Conjugation of metal-binding G5H sequence to GFP-fluorophore peptide enhanced the action of Cu2+ on quenching of intrinsic fluorescence due to Y residue. Two other Y-containing peptides, TYG-G5H and SYG-G5H, also showed intrinsic fluorescence which is sensitive to addition of Cu2+. There was linear relationship between the loading of Cu2+ and the quenching of fluorescence in these peptide, suggesting that Cu2+-dependent quenching of Y-reside-derived fluorescence could be a measure of copper occupancy in the peptides. Lastly, the fate of Y residue in the Cu-loaded peptides under oxidative condition in the presence of H2O2 was discussed based on the Cu/H2O2-dependent changes in fluorescence spectra.